Targeting endoplasmic reticulum stress‐induced lymphatic dysfunction for mitigating bisphosphonate‐related osteonecrosis - Ziyue Qin; Hanyu Xie; Pengcheng Su; Zesheng Song; Rongyao Xu; Songsong Guo; Yu Fu; Ping Zhang; Hongbing Jiang (Clinical and Translational Medicine)
Abstract Background Bisphosphonates (BPs) are the first‐line treatment to stop bone resorption in diseases, including osteoporosis, Paget's disease, multiple myeloma and bone metastases of cancer. However, BPs‐related osteonecrosis of the jaw (BRONJ), characterized by local inflammation and jawbone necrosis, is a severe intractable complication. The cumulative inflammatory burden often accompanies impaired lymphatic drainage, but its specific impact on BRONJ and the underlying mechanisms remain unclear. Methods The mouse BRONJ model was established to assess the integrity and drainage function of lymphatic vessels by tissue clearing techniques, injected indocyanine green lymphatic clearance assay, flow cytometry analysis and histopathological staining. RNA sequencing, metabolome analysis, transmission electron microscopy and Western blotting were utilized to analyze the impacts of Zoledronate acid (ZA) on endoplasmic reticulum stress (ERS) and function of lymphatic endothelial cells (LECs). By constructing Lyve1creERT; SIRT6f/f and Lyve1creERT; ATG5f/f mice, we evaluated the role of ERS‐induced LECs apoptosis in the progression of BRONJ. Additionally, we developed a nanoparticle‐loaded ZA and rapamycin (ZDPR) to enhance autophagy and evaluated its potential in mitigating BRONJ. Results The mouse BRONJ model displayed impaired lymphatic drainage, accompanied by significant local inflammation and bone necrosis. The prolonged stimulation of ZA resulted in the extension of ERS and the inhibition of autophagy in LECs, ultimately leading to apoptosis. Mechanistically, ZA activated XBP1s through the NAD+/SIRT6 pathway, initiating ERS‐induced apoptosis in LECs. The conditional knockout mouse models demonstrated that the deletion of SIRT6 or ATG5 significantly worsened lymphatic drainage and inflammatory infiltration in BRONJ. Additionally, the innovative nanoparticle ZDPR alleviated ERS‐apoptosis in LECs and enhanced lymphatic function, facilitating inflammation resolution. Conclusion Our study has elucidated the role of the NAD+/SIRT6/XBP1s pathway in ERS‐induced apoptosis in ZA‐treated LECs, and further confirmed the therapeutic potential of ZDPR in restoring endothelial function and improving lymphatic drainage, thereby effectively mitigating BRONJ. Key points Bisphosphonate‐induced lymphatic drainage impairment exacerbates bone necrosis. Zoledronate acid triggers endoplasmic reticulum stress and apoptosis in lymphatic endothelial cells via the NAD+/SIRT6/XBP1s pathway. Novel nanoparticle‐loaded Zoledronate acid and rapamycin enhances autophagy, restores lymphatic function, and mitigates bisphosphonates‐related osteonecrosis of the jaw progression.